CONGRATULATIONS ON THE ANNIVERSARY: GLOBENKO GALINA MICHAILOVNA (TO THE 80TH ANNIVERSARY SINCE BIRTH) - Irina A. Bulankina; Tamara I. Shalina; Vladimir G. Izatulin; Anna N. Sinelnikova; Irina N. Gerasimova; Olga N. Shashkova (Байкальский медицинский журнал)
An excellent teacher and mentor Galina Mikhailovna Globenko has been working at the Department of Human Anatomy, Operative Surgery and Forensic Medicine of Irkutsk State Medical University for more than half a century. Galina Mikhailovna was born on February 21, 1944 in the village of Tumanny, Srednekansky district, Khabarovsk Territory.She spent her childhood and primary school years in Chukotka, in the city of Pevek and in the village of Bodaibo, where Galina Mikhailovna graduated from high school and in 1961 entered the Irkutsk State Medical Institute.After graduating from medical institute, Galina Mikhailovna was invited to the department of normal human anatomy, where she proved herself to be a conscientious and responsible worker, actively participated in the work of the department’s team, continued her education in graduate school and soon defended her Ph.D. thesis.During her career, Galina Mikhailovna went from assistant to associate professor of the department, was secretary of the Bureau of Rationalization and Invention, and worked in the dean’s office of the medical faculty of the medical university.